Looking for solutions: students' use of infrared cameras in calorimetry labs. Issue 1 (1st November 2022) - Samuelsson, Christopher Robin; Ho, Felix M.; Elmgren, Maja; Haglund, Jesper
Abstract : This study adds to the growing body of research on laboratory work. The study involves four pairs of students in a university introductory calorimetry lab of which two pairs, the IR-pairs (infrared camera-pairs), were given access to infrared cameras to use however they liked during their course lab work. Two other pairs, the T-pairs (thermometer-pairs), were not given access to infrared cameras during their course lab work. The IR-pairs were video recorded when they chose to use the IR cameras and the T-pairs were video-recorded during the corresponding sequences. Additionally, all pairs participated in a modified lab after their course lab, in which the pairs had access to IR cameras and were presented with the same phenomena although with equipment modified to better accommodate for the use of IR cameras (thin plastic cups were used instead of calorimeters). Students' practice, communication and reasoning was studied to explore how the IR cameras affect students' activity. The results show that the access to IR cameras led to a reasoning focused on a macroscopic level of chemistry knowledge, involving heat transfer to the surrounding and measurement errors, and that the lab practice of most of the students was continuous (rather than intermittent) when they had access to IR cameras. We conclude by arguing that the access to IR cameras affects students' conceptual and epistemological framing of the lab, i.e. that the students perceive the lab activity differently when they get access to IR cameras (both in a conceptual and epistemological sense). As an implication for teaching, we suggest that giving students access to IR cameras in a chemistry lab may be a way to introduce flexibility in the degree of openness of the lab.